2005
DOI: 10.1115/1.2113047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scanning Schemes on Laser Tube Bending

Abstract: Four laser scanning schemes for tube bending, including point-source circumferential scanning, pulsed line-source axial procession, and line-source axial scanning without and with water cooling are investigated in numerical simulation. The coupled thermomechanical model established using the finite element method is validated and applied to predict the bending deformation and help better understand bending mechanisms under different schemes. The influence of important parameters such as beam coverage, scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Single axial scanning with a line source is expected to give much higher bending angle compared to multiple circumferential scanning with point laser source. Many variations of these primary 8.6 Advances in Laser Forming 345 laser schemes are possible depending on the source of laser (point or line source, and continuous or pulsed beam) and application of water cooling (with or without water cooling) (Zhang et al 2006). The primary mechanism of laser tube bending during circumferential scanning is generally considered as UM.…”
Section: Laser Forming Of Tubesmentioning
confidence: 99%
“…Single axial scanning with a line source is expected to give much higher bending angle compared to multiple circumferential scanning with point laser source. Many variations of these primary 8.6 Advances in Laser Forming 345 laser schemes are possible depending on the source of laser (point or line source, and continuous or pulsed beam) and application of water cooling (with or without water cooling) (Zhang et al 2006). The primary mechanism of laser tube bending during circumferential scanning is generally considered as UM.…”
Section: Laser Forming Of Tubesmentioning
confidence: 99%
“…Circumferential and axial scanning were compared numerically and experimentally by Zhang et al [6]. Safdar et al [7] compared both methods under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, these parameters have been optimized under the shortening mechanism which researchers believe is the dominant mechanism [2,3,6,7]. In the shortening mechanism, the tube diameter to beam diameter ratio is considered large for homogeneous heating in the thickness direction of the tube.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that a high scanning speed was useful to achieve uniform bending deformations for the varying thickness plate due to the difference of peak temperature and temperature gradient between thickness and thinner locations. Zhang et al (2006) examined the effects of scanning schemes on laser tube bending. They showed that in line‐source axial scanning, within a certain velocity range, high scanning velocity could produce large deformation while the water cooling was helpful to increase the bending deformation.…”
Section: Introductionmentioning
confidence: 99%